Cabaran yang dihadapi oleh Jabatan Kebudayaan Kesenian dan Warisan Negeri Pulau Pinang dalam menerapkan penghayatan dan kesedaran teater tradisional boria dalam kalangan golongan belia Pulau Pinang - Thavamalar, A/P Tausee Ganu (Universiti Malaysia Sarawak (UNIMAS), 2007)
Boria is a form traditional theatre performed on stage. It is very popular in Northern Malaysia, especially in Penang. In the old days, Boria performances were held to boost the Malay community’s spirit in fighting for their rights. As a whole, this research aims to study the challenges faced by Department of Culture, Arts and Heritage in trying to increase the awareness of Boria theatre among the youth in Penang.